1992
DOI: 10.1177/106002809202600113
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Contrast Media following Cardiac Angiography: Pathogenesis, Clinical Course, and Preventive Measures, Including the Role of Low-Osmolality Contrast Media

Abstract: Whether the incidence of CAN following cardiac angiography is reduced with LOCM remains controversial. The incidence of CAN in patients with normal renal function does not appear to differ in patients treated with LOCM versus HOCM because few patients in each group develop renal failure. Additional controlled clinical trials comparing CAN of LOCM and HOCM in patients with renal dysfunction are needed. Because of greater product cost and scarcity of documented benefit compared with HOCM, selection of LOCM based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…In a large randomized trial comparing the nephrotoxic effects of nonionic vs. ionic contrast media, it was found that in patients with baseline serum creatinine levels of > I .5 mg%, there was a 7% incidence of CIN (rise of 2 1.0 mg%) when an ionic contrast agent was used vs. 3% when a nonionic contrast agent was used [27]. Other studies have not shown this effect, but they may be limited by methodologic factors including small sample size and small percentage of high-risk patients being studied [35].…”
Section: Pre-existing Renal Dysfunction It Is Widely and Ap-mentioning
confidence: 96%
“…In a large randomized trial comparing the nephrotoxic effects of nonionic vs. ionic contrast media, it was found that in patients with baseline serum creatinine levels of > I .5 mg%, there was a 7% incidence of CIN (rise of 2 1.0 mg%) when an ionic contrast agent was used vs. 3% when a nonionic contrast agent was used [27]. Other studies have not shown this effect, but they may be limited by methodologic factors including small sample size and small percentage of high-risk patients being studied [35].…”
Section: Pre-existing Renal Dysfunction It Is Widely and Ap-mentioning
confidence: 96%
“…Patients with an acute myocardial infarction (non-ST elevation myocardial infarction or ST elevation myocardial infarction) have the added risk factor of suboptimal heart functioning that can predispose them to CIRD. [1][2][3][4][5][7][8][9] …”
mentioning
confidence: 99%
“…1,2 The incidence of CIRD has been shown to range from 10% to 40% after coronary angiography in patients with preexisting renal insufficiency. 2,3 The risk of renal dysfunction after contrast media exposure is increased with the presence of other disease states that alter or impair renal function, for example, diabetes mellitus and hypertension. [1][2][3][4][5][6][7] Many of these comorbidities may be present in the population who present with an ACS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lautin et al (35) have reported that LOCM induces nephropathy less frequently than HOCM. However, controversial data have been reported by other investigators (36,37). A meta-analysis of data from 25 clinical studies showed that the incidence rate of radiocontrast nephropathy is significantly lower in LOCM than in HOCM, in which the odds ratio is 0.5 in patients with pre-existing renal impairment and 0.75 in those with normal renal function in favor of LOCM (38).…”
Section: Osmolalitymentioning
confidence: 93%